THE CHEMICAL COMPOSITION AND NUTRITIVE VALUE OF Brachiaria GRASS CULTIVARS AT KATUMANI DRYLAND RESEARCH STATION IN SOUTH EASTERN KENYA (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
The study was conducted at Kenya Agricultural and Livestock Research Organisation, Katumani, Machakos to evaluate the herbage quality of Brachiaria grass cultivars in semi arid regions of Eastern Kenya. Brachiaria cultivars namely B. decumbens cv. Basilisk, Brachiaria hybrid  Mulato II, four Brachiaria brizantha cultivars Marandu, Xaraes, Piata, MG4 and Brachiaria humidicola cv Llanero were assessed with reference to their chemical and nutritive composition at 22, 24 and 28 weeks post seedling emergence. Rhodes grass (Chloris gayana cv KATR3) and Napier grass (P. pupureum cv. Kakamega I) were included as controls. There were significant differences (p